On resource complementarity in activity networks: further results - Silva, Hélder C. (2010)
We address the issue of optimal resource allocation, and more specifically, the analysis of complementarity of resources (primary resource or P-resource and supportive resource or S-resource) to activities in a project. We developed a mathematical model capable of determining the ideal mixture of resources allocated to the activities of a project, such that the project is completed with minimal cost. This problem has a circularity issue that greatly increases its complexity. We have developed a procedure which we illustrate by application to small instances of the problem, using complete enumeration over the decision space. The development of a more computationally efficient procedure awaits the second phase of this study.